Servant leadership and work culture as determinants of employee performance improvement - Slamet Riyanto; Fauji Sanusi; Liza Mumtazah Damarwulan (Institute of Computer Science (IOCS), 2023)
This study aims to examine the influence and analyze the factors that can improve employee performance. Namely, the variables of servant leadership, work culture, and organizational commitment can mediate an increase in employee performance related to services at the Jakarta PSDKP Base. The study used a quantitative approach with saturated sampling techniques using questionnaires, a population of 136 employees, and SEM PLS 4.0 as a statistical tool. The results showed that servant leadership has a significant effect on employee performance, there is a substantial effect of work culture on employee performance, there is a considerable effect of servant leadership on organizational commitment, work culture has a significant impact on organizational commitment, organizational commitment has a significant effect on employee performance. Organizational commitment can mediate the impact of servant leadership on employee performance. According to the executive level, managerial implications are made using the POLC concept (Planning, Organizing, Leading, and Controlling). This research is expected to make a theoretical contribution to the literature in this context, among others, in human resource management.